Swiss market access in a global trade war - Alessandro Nicita; Marcelo Olarreaga; Peri Silva; Jean-Marc Solleder (Aussenwirtschaft, 2019)
We measure the extent to which Swiss market access would be affected in a global trade war. After calculating the change in tariffs at the tariff-line level that Swiss exporters would face in a trade war, we then aggregate them at the industry, destination market, and global level using theoretically well-grounded aggregation methods first introduced by Anderson and Neary (1996). Our results suggest that Swiss market access will be seriously jeopardized in the event of a global trade war, with an increase in tariffs faced by Swiss exporters of 34 percentage points. The largest increases in tariffs would be experienced in large destination markets where Swiss exporters currently benefit from low export barriers (the European Union, the United States and Japan). Chemicals, machinery, professional and scientific equipment, and food experience above average increases in tariff barriers.
Keywords: F13; 330; trade war; Swiss market access